Righteously Entertaining: Punishing and Constructing Society's Moral Reality with Online Public Shamings - Ferreira Dias Tavares, Inês (Université d'Ottawa / University of Ottawa, 2026)
Online public shamings are a contemporary phenomenon in which someone's wrongdoing is publicized online, attracting the attention of a mass audience, which reacts to it, shaming the person and pressuring employers and business partners to cut ties with the culprit. Trying to avoid prejudgements on the phenomenon's ethics, this thesis explores how online public shamings develop. The investigation starts by defining the phenomenon based on five empirical cases and on the existing literature. Based on this definition and initial characteristics, two other similar phenomena were approached from a theoretical perspective, in search of a comprehensive lens for the online public shamings: moral crusades and charivaris. Based on these two phenomena, online public shamings were conceptualized as movements of deviance creation, in which online imagined communities battle to extend their rules and values to opposing publics, and at the same time they punish an individual for breaking a cherished value. By using mixed methods to analyse Twitter data, a single case study was developed. The empirical analysis revealed that online shamers are composed of several different groups, with different types of interests, both opportunistic and righteous. In the latter group, Black Twitter revealed itself as morally engaged with expanding anti-racist rules in American society. The punishment of the shamed, in this sense, represents another episode in a larger movement for social equality in America. The process of deviance creation, nonetheless, is marked by the use of punishment as entertainment and the imposition of rules and consequences without any democratic due process. Even though more research is needed to expand the conclusions of this work, this case study provides an initial framework for the development of basic aspects of online public shamings.
Keywords: Online public shaming; Cancel culture; Moral Crusades; Charivari; Social Media; Surveillance